Strategies of tree species to adapt to drought from leaf stomatal regulation and stem embolism resistance to root properties - Chen, Zhicheng; Li, Shan; Wan, Xianchong; Liu, Shirong (Frontiers in Plant Science, 2022)
Considerable evidences highlight the occurrence of increasing widespread tree mortality as a result of global climate change-associated droughts. However, knowledge about the mechanisms underlying divergent strategies of various tree species to adapt to drought has remained remarkably insufficient. Leaf stomatal regulation and embolism resistance of stem xylem serves as two important strategies for tree species to prevent hydraulic failure and carbon starvation, as comprising interconnected physiological mechanisms underlying drought-induced tree mortality. Hence, the physiological and anatomical determinants of leaf stomatal regulation and stems xylem embolism resistance are evaluated and discussed. In addition, root properties related to drought tolerance are also reviewed. Species with greater investment in leaves and stems tend to maintain stomatal opening and resist stem embolism under drought conditions. The coordination between stomatal regulation and stem embolism resistance are summarized and discussed. Previous studies showed that hydraulic safety margin (HSM, the difference between minimum water potential and that causing xylem dysfunction) is a significant predictor of tree species mortality under drought conditions. Compared with HSM, stomatal safety margin (the difference between water potential at stomatal closure and that causing xylem dysfunction) more directly merge stomatal regulation strategies with xylem hydraulic strategies, illustrating a comprehensive framework to characterize plant response to drought. A combination of plant traits reflecting species’ response and adaptation to drought should be established in the future, and we propose four specific urgent issues as future research priorities.